COPYRIGHT AND REMIX ATTITUDES IN DIGITAL SPACES: HOW DO THEY DIFFER WITH AGE, EXPERIENCE AND KIND OF USE? - Aufderheide, Patricia Ann; Sinnreich, Aram; Milosevic, Tijana; Burroughs, Benjamin (AoIR Selected Papers of Internet Research, 2015)
How do the affordances of digital technology to copy and share information facilitate change in attitudes toward the creative process and copyright? How do custom and law affect use, and how does technology-afforded use affect custom and law? How does education about law and custom change behavior and attitudes? Despite commonly held misconceptions about stark generational and digital divides in attitudes about copyright and cultural appropriation, and contrary to widespread and reductionist claims about piracy and plagiarism, recent communication research reveals that cultural approaches to copyright’s most contentious arena – copying and reuse of copyrighted material – are nuanced, evolving and, at times, conflicting. This panel showcases current research on behavior both of consumers and creators, looking at how age, experience, social location and use behavior play a role in copyright attitudes. Research of the various panelists is presented under the umbrella of a science and technology studies (STS) approach, which considers the interaction between users and the mediating technologies that provide them digital access, and how this interaction conditions their attitudes and actions. Research showcased on this panel draws from analysis of behavior of demographically complex groups over time, both as creators and as consumers. Specifically, one study examines the creative decisions and gatekeeper interactions that involve copyrighted material of documentary filmmakers over the decade 2004-2014, as seen through both survey and qualitative data. Another compares two surveys, from 2009 and 2014, of communication scholars on scholarly research decision-making before and after creating a best practices code to clarify fair use for the field. A third analyzes creative decisions of visual arts professionals in four fields—art production, art scholarship, scholarly book and journal production, and museum exhibition creation—around use of copyrighted material. The fourth study analyzes attitudes of users of streaming media, building on ethnographic data about of audience usage of streaming and interviews with industry leaders, drawing links between experience with streaming media early in life and copyright attitudes. Variables include age, experience, type of digital media creation and use, and familiarity with the law. Results from the different studies demonstrate the importance of basing generalizations on specific fields of practice and types of experience. These presentations demonstrate the value of close analysis of behavior and attitudes to demystify a highly politicized public debate plagued by moral panic, and they also provide a baseline for future research.